Clinical Significance of De Novo and Inherited Copy-Number Variation - Vulto-van Silfhout, A; Hehir-Kwa, J; van Bon, B; Schuurs-Hoeijmakers, J; Meader, S; Hellebrekers, C; Thoonen, I; de Brouwer, A; Brunner, H; Webber, C; Pfundt, R; de Leeuw, N; et al. (2013)
Copy-number variations (CNVs) are a common cause of intellectual disability and/or multiple congenital anomalies (ID/MCA). However, the clinical interpretation of CNVs remains challenging, especially for inherited CNVs. Well-phenotyped patients (5,531) with ID/MCA were screened for rare CNVs using a 250K single-nucleotide polymorphism array platform in order to improve the understanding of the contribution of CNVs to a patients phenotype. We detected 1,663 rare CNVs in 1,388 patients (25.1%; range 0-5 per patient) of which 437 occurred de novo and 638 were inherited. The detected CNVs were analyzed for various characteristics, gene content, and genotype-phenotype correlations. Patients with severe phenotypes, including organ malformations, had more de novo CNVs (P < 0.001), whereas patient groups with milder phenotypes, such as facial dysmorphisms, were enriched for both de novo and inherited CNVs (P < 0.001), indicating that not only de novo but also inherited CNVs can be associated with a clinically relevant phenotype. Moreover, patients with multiple CNVs presented with a more severe phenotype than patients with a single CNV (P < 0.001), pointing to a combinatorial effect of the additional CNVs. In addition, we identified 20 de novo single-gene CNVs that directly indicate novel genes for ID/MCA, including ZFHX4, ANKH, DLG2, MPP7, CEP89, TRIO, ASTN2, and PIK3C3. © 2013 WILEY PERIODICALS, INC.